On the "margins" of empire? Toward a history of Hawaiian labour and settlement in the Pacific Northwest. - Calnitsky, Naomi (Waka Kuaka, 2017)
This paper explores the historiography of Hawaiian mobility in the 19th century, with reference to mobilities that took place through Kānaka Maoli engagements as servants for the Hudson's Bay Company of London. In recharting Hawaiian mobilities to the Pacific Northwest, it considers how Kānaka Maoli histories were intertwined with trans-Pacific networks of commerce and a broader Pacific world of aspirational mobility, extractive marine-based industries, and ultimately, a land-based fur trade centered initially at Fort Astoria. It discusses how Hawaiian engagements with the HBC in the Pacific Northwest were formative for their eventual incorporation into the colonial settler world of British Columbia, and examines their displacement from Oregon Territory in the wake of the 1846 boundary settlement. It incorporates themes of intimacy, encounter and hierarchy as key sites for locating Hawaiian social histories along the Northwest Coast. Finally, the Hawaiian presence in British Columbia is traced with attention to community formation and land acquisition. Whether or not they fit within a broader category of pioneer-settlers, the "Kanakas" displaced to the Northwest Coast were for a time first positioned along what historian Adele Perry has termed the "ragged margins" of empire.